2D SnS2 Nanostructure-Derived Photocatalytic Degradation of Organic Pollutants Under Visible Light - Srivastava, Rohit Ranjan; Kumar Vishwakarma, Pramod; Yadav, Umakant; Rai, Suyash; Umrao, Sima; Giri, Rajiv; Saxena, Preeti Suman; Srivastava, Anchal (Frontiers in Nanotechnology, 2021)
Wastewater produced by the textile industry contains various dyes and organic compounds that directly or indirectly affect surface water or groundwater pollution. Visible-light-driven semiconductor photocatalysis is the leading pathway for the degradation of environmental pollutants. Herein we report the bottom-up hydrothermal growth of 2D tin disulfide nanostructures (SnS2 NSs) for the efficient photodegradation of organic pollutants such as Rhodamine B (Rh.B) and Methyl Violet (M.V) in an aqueous medium under visible light (λ > 400 nm) irradiation. The as-synthesized SnS2 NSs were characterized by various structural, morphological, and optical techniques such as XRD, RAMAN, TEM, UV–Vis, Brunauer–Emmett–Teller, etc. Furthermore, the low bandgap (∼1.6 eV), the high surface area (56 m2/g), and the anionic nature of SnS2 NSs attribute to it as an efficient photocatalyst for photocatalytic applications. The photocatalytic properties of SnS2 NSs showed good degradation efficiency of 94 and 99.6% for Rh. B and M.V, respectively, in 25 min. The kinetic rate constant of these dyes was estimated by using the Langmuir–Hinshelwood model. Here we also performed the recyclability test of the photocatalyst and discussed the plausible mechanism for the photocatalytic degradation of organic pollutants. The XPS spectra of SnS2 NSs were studied before and after the photodegradation of Rh.B and M.V, indicating the high stability of the photocatalyst. Moreover, in vitro cytotoxicity was also evaluated against human cervical cancer cell lines (HeLa cells) with different concentrations (0–1,000 μg/ml) of as-synthesized SnS2 NSs. This intended work provides a possible treatment for the degradation of organic pollutants under visible light to balance the aquatic ecosystems.